2020
DOI: 10.1101/2020.05.03.20089078
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of long-term non-pharmaceutical interventions on COVID-19 epidemic dynamics and control

Abstract: Non-pharmaceutical interventions to combat COVID-19 transmission have worked to slow the spread of the epidemic but can have high socio-economic costs. It is critical we understand the efficacy of nonpharmaceutical interventions to choose a safe exit strategy. Many current models are not suitable for assessing exit strategies because they do not account for epidemic resurgence when social distancing ends prematurely (e.g., statistical curve fits) nor permit scenario exploration in specific locations. We develo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…The body of modeling work based on the SEIR scheme touches similar themes to those just mentioned, but due to the larger number of articles, there are also some new interesting angles. In particular, we find papers focusing, among other things, on the effects of face masks [82] , [85] , [86] , [87] , [89] , capturing different aspects of NPIs [64] , [67] , [69] , [70] , [71] , [73] , [74] , [75] , [77] , [79] , [80] , [81] , [83] , [84] , [90] , studying the problem of optimal control of the pandemic [72] , [76] , [78] , [88] , investigating approaches to lift measures put in place in the first wave [62] , [63] , [65] , model the possible exposure to the virus via droplets or fomites [91] , [92] , and consider the impact on the health care infrastructure of COVID-19 and seasonal flu in the winter [68] .…”
Section: Epidemic Modelsmentioning
confidence: 99%
“…The body of modeling work based on the SEIR scheme touches similar themes to those just mentioned, but due to the larger number of articles, there are also some new interesting angles. In particular, we find papers focusing, among other things, on the effects of face masks [82] , [85] , [86] , [87] , [89] , capturing different aspects of NPIs [64] , [67] , [69] , [70] , [71] , [73] , [74] , [75] , [77] , [79] , [80] , [81] , [83] , [84] , [90] , studying the problem of optimal control of the pandemic [72] , [76] , [78] , [88] , investigating approaches to lift measures put in place in the first wave [62] , [63] , [65] , model the possible exposure to the virus via droplets or fomites [91] , [92] , and consider the impact on the health care infrastructure of COVID-19 and seasonal flu in the winter [68] .…”
Section: Epidemic Modelsmentioning
confidence: 99%
“…Equation (4) is a six-parameter model – the parameters are m 0 , N, μ 1 , μ 3 , τ 1 and τ 2 . Among these, the last two are well-known – they are about 7 days and 3 days respectively [21]. These are values we shall use throughout the entirety of this Article .…”
Section: The Baseline Modelmentioning
confidence: 99%
“…Rather, we give the values of X and hence of the capture probability P 3 X or 1− μ 3 for some realistic sets of parameter values. With the standard values 7 and 3 for τ 1 and τ 2 and taking τ 4 = 4 (the total incubation period is approximately 7 days on average [21]), the value τ 3 = 2 gives T = 1/6. This implies that contact traced cases remain at large for a relatively short time.…”
Section: Public Health Intervention Effectsmentioning
confidence: 99%
“…[17] we have shown that contact tracing will indeed capture only a small percentage of total cases if the asymptomatic fraction is high; moreover, contact tracing is managed by healthcare professionals many of whom will now be re-deployed to vaccination drive. We use the parameter values [S1] τ 1 = 7 and τ 2 = 3, so that the function n gets defined as We assume that vaccinated cases have the same μ 1 , τ 2 and τ 1 as non-vaccinated ones (details in §2), so that we can use this function n to count at large cases of both unvaccinated and vaccinated groups. Putting all this together, we have the equation with the second line being a simple rearrangement of the first.…”
Section: Supplementary Datamentioning
confidence: 99%